GE_GERICHTE C/16374/2016 vom 23. Januar 2018 - GE Cour de justice (2018)
PROTECTION DE L'UNION CONJUGALE ; MESURE PROVISIONNELLE ; RETRAIT DU DROIT DE GARDE ; VISITE | CPC.298.al1; CC.273.al1; CC.310.al1